Identification of differentially expressed circular RNAs in human monocyte derived macrophages response to Mycobacterium tuberculosis infection. Issue 1 (December 2017) - Huang, Zikun; Su, Rigu; Deng, Zhen; Xu, Jianqing; Peng, Yiping; Luo, Qing; Li, Junming
Abstract Macrophages act as the first line of host immune defense againstMycobacterium tuberculosis (Mtb). Recent studies have demonstrated circular RNAs (circRNAs) are implicated in a variety of physiological and pathological processes; however, the role of circRNAs in macrophages response to Mtb infection remain unknown. To address this issue, here we characterized circRNAs expression profiles in human monocyte derived macrophages (MDMs) response to Mtb infection using microarray assay. Our results revealed that many circRNAs were differentially expressed in human MDMs after Mtb infection; of these, 32 circRNAs were up-regulated and 110 were down-regulated. Real time PCR results were generally consistent with the microarray data. Furthermore, we found that hsa_circ_0043497 and hsa_circ_0001204 may be effective diagnostic biomarkers for TB. This study provides the first evidence that circRNAs alterations are involved in human MDMs response to TB infection and reveal potential targets for diagnostics and the treatment of TB.